Sovereign to corporate risk spillovers - Patrick Augustin; Hamid Boustanifar; Johannes Breckenfelder; Jan Schnitzler (European Central Bank (ECB), 2016)
Using the announcement of the first Greek bailout on April 11, 2010, we quantify significant spillover effects from sovereign to corporate credit risk in Europe. A ten percent increase in sovereign credit risk raises corporate credit risk on average by 1.1 percent after the bailout. These effects are more pronounced in countries that belong to the Eurozone and that are more financially distressed. Bank dependence, public ownership and the sovereign ceiling are channels that enhance the sovereign to corporate risk transfer.
Keywords: F34; F36; G15; H81; G12; 330; bailout; contagion; credit risk; Greece; risk transmission